Association of systemic inflammation with survival in patients with cancer cachexia: results from a multicentre cohort study. Issue 6 (2nd August 2021) - Zhang, Qi; Song, Meng‐Meng; Zhang, Xi; Ding, Jia‐Shan; Ruan, Guo‐Tian; Zhang, Xiao‐Wei; Liu, Tong; Yang, Ming; Ge, Yi‐Zhong; Tang, Meng; Li, Xiang‐Rui; Qian, Liang; et al.
Abstract: Background: Although systemic inflammation is an important feature of the cancer cachexia, studies on the association between systemic inflammation and prognostic of cancer cachexia are limited. The objective of this study is to evaluate whether the neutrophil‐to‐lymphocyte ratio (NLR) is associated with outcome and quality of life for patients with cancer cachexia and investigated any interaction between NLR and the clinical parameters. Methods: This is a multicentre cohort study of 2612 cancer patients suffering from cachexia diagnosed between June 2012 and December 2019. The main parameters measured were overall survival (OS) time and all‐cause mortality. The association between NLR and all‐cause mortality was evaluated using hazard ratios (HRs) and the restricted cubic spline model with a two‐sided P ‐value. Optimal stratification was used to solve threshold points. We also evaluated the cross‐classification of NLR for each variable of survival. Results: Of the 2612 participants diagnosed with cancer cachexia, 1533 (58.7%) were male, and the mean (SD) age was 58.7 (11.7) years. Over a median follow‐up of 4.5 years, we observed 1189 deaths. The overall mortality rate for patients with cancer cachexia during the first 12 months was 30.2% (95%CI: 28.4%–32.0%), resulting in a rate of 226.07 events per 1000 patient‐years. An increase in NLR had an inverted L‐shaped dose–response association with all‐cause mortality. The optimal cut‐off point for NLR as a predictor of mortality in cancer patients with cachexia was 3.5. An NLR of 3.5 or greater could independently predict OS (HR, 1.51, 95%CI: 1.33–1.71). These associations were consistent across subtypes of cancer. Several potential effect modifiers were identified including gender, BMI, tumour type, KPS score and albumin in content. Increasing NLRs were independently associated with a worsening in the majority of EORTC QLQ‐C30 domains. Elevated baseline NLR was associated with low response and poor survival in patients treated with immunotherapy. Conclusions: The baseline NLR status was found to be a significant negative prognostic biomarker for patients with cachexia; this effect was independent of other known prognostic factors.